Quantitative Farming Systems Analysis: A multi-level case study in Malawi: Prioritizing, tailoring, and targeting socio-technical innovation bundles towards the Sustainable Intensification of Mixed Farming Systems - Cossu, A.; Frelat, Romain; Hammond, James; Zepeda, E. A.; Sonder, Kai; Lopez-Ridaura, Santiago; Groet, J.; Wijk, Mark T. van (International Institute of Tropical Agriculture, 2024)
The MFS initiative adopts a unique research approach, focusing on the entire mixed farming system rather than specific components like agronomy or economics. Small-scale farmers in the global South, involved in various farming activities, inherently grasp the holistic understanding of their interconnected system. This highlights the need for research and development projects to consider and incorporate this holistic understanding.